Investigation On The Properties Of Rubber Vulcanizates For Anti-Vibration Applications Effects Of Different Rubber And Particle Size Of Carbon Black - Shukri, Nafeesa Mohamad (2019)
Most of the automotive industry facing a major challenge to meet the changing demands in material specifications, performance and durability requirements. In designing rubber for anti-vibration application, the mechanical and dynamic properties are required in order to obtain good damping properties and eliminate the overestimation of the vibration of the resonant frequency of the system. This research work focused on the effect of different rubber types (unfilled) SMR 60 CV, SMR L, RSS, SBR, NBR, CR and EPDM and particle size of carbon black (filled) N220, N330, N550, N774 and N990 with SMR 60 CV rubber on the mechanical and dynamic properties. The curing characteristic, mechanical properties (tensile test, compression set, fatigue), and dynamic properties (static and dynamic stiffness, tan delta) were analyzed. The curing characteristic results show the relationship of unfilled compounds with rubber bond energy. The longer cure time indicates longer times to break the higher bond energy of the rubber chain. Meanwhile, for the filled compound, the cure rates gradually increased with the lower carbon black surface area due to the diffusion limitation and lower chain mobility. The dynamic properties results based on the Payne effect theory influenced by the rubber bond structure that gave higher value of dynamic stiffness due to the better rubber-rubber interaction. For the filled compound, higher surface area of carbon black gave higher dynamic stiffness due to increase in rubber-filler and filler-filler interactions. Thus, the rubber viscoelasticity and carbon black particle size play a big role and a major concern in designing the compound formulation for rubber anti-vibration applications.